Petrography and provenance of Upper Cretaceous – Palaeogene sandstones in the foreland basin system of Central Nepal. Issue 2 (25th January 2018) - Neupane, Bhupati; Ju, Yiwen; Allen, Charlotte M.; Ulak, Prakash Das; Han, Kui
ABSTRACT: Sedimentary deposits of the Cretaceous to Miocene Tansen Group of Lesser Himalayan association in central Nepal record passive-margin sedimentation of the Indian Continent with direct deposition onto eroded Precambrian rocks (Sisne Formation onto Kaligandaki Supergroup rocks), succeeded by the appearance of orogenic detritus as the Indian continent collided with Asia on a N-dipping subduction zone. Rock samples from two field traverses were examined petrographically and through detrital zircon U–Pb dating, one traverse being across the Tansen Group and another across the Higher and Tethyan Himalaya (TH). The Tansen Group depositional ages are well known through fossil assemblages. We examined samples from three units of the Tansen Group (Amile, Bhainskati, and Dumri Formations). The Sedimentary petrographic data and Qt F L and Qm F Lt plots indicate their 'Quartzose recycled' nature and classify Tansen sedimentary rocks as 'recycled orogenic', suggesting Indian cratonic and Lower Lesser Himalayan (LLH) sediments as the likely source of sediments for the Amile Formation (Am), the TH and the Upper Lesser Himalaya (ULH) as the source for the Bhainskati Formation (Bk), and both the Tethyan and Higher Himalaya (HH) as the major sources for the Dumri Formation (Dm). The Cretaceous–Palaeocene pre-collisional Am is dominated by a broad detrital zircon U–Pb ~1830 Ma age peak with neither Palaeozoic nor Neoproterozoic zircons grains, but hosts a significant proportion (23%) of syndepositional Cretaceous zircons (121–105 Ma) would be contributions from the LLH volcanosedimentary arc, Gangdese batholith (including the Xigaze forearc). The other formations of the Tansen Group are more similar to Tethyan units than to Higher Himalaya Crystalline (HHC). From the analysed samples, there is a lack of distinctive evidence or HH detritus in the Tansen basin. Furthermore, the presence of ~23±1 Ma zircons from the HH unit suggests that they could not have been exposed until the earliest Miocene time.